Carcinoma Breast with Cerebellar Dysfunction Paraneoplastic Syndrome: A Rare Case Presentation - Anand Prasath Jayachandiran (Research Highlights in Disease and Health Research Vol. 4, 2023)
We present a case of a 52-year-old female with carcinoma breast and symptoms and signs of cerebellar dysfunction, which was later determined to be anti-YO autoantibody positive paraneoplastic syndrome. Paraneoplastic Syndrome, as Paraneoplastic cerebellar degeneration (PCN), in carcinoma breast is a rare entity due to the autoimmune responses. The patients’ neurological symptoms progressed in spite of chemotherapy, steroids and surgical removal of the initiating tumor and became wheelchair bound. Despite surgical and chemotherapy treatment, the patient’s neurological condition worsened, indicating a poor prognosis.